2014
DOI: 10.1109/msp.2014.2312099
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Interpretation of Scattering Mechanisms in Polarimetric Synthetic Aperture Radar: Advances and perspectives

Abstract: P olarimetric target decomposition is a powerful technique to interpret scattering mechanisms in polarimetric synthetic aperture radar (PolSAR) data. Eigenvalueeigenvector-based and model-based methods are two main categories within the incoherent decomposition techniques. Eigenvalue-eigenvector-based decomposition becomes relatively mature since it has a clearer mathematical background and has only one decomposition solution. In contrast, model-based decompositions can obtain different decomposition solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 32 publications
0
68
0
Order By: Relevance
“…In past decades, this technique has been widely used in many different applications, such as land-cover classification, target detection, damage assessment, and soil moisture estimation [4]. Target decomposition mainly includes two categories: coherent decomposition of the measured Sinclair matrix, and incoherent decomposition of the measured coherency/covariance matrix [1]- [4]. Because of the diversity of scattering models and parameter inversion algorithms, model-based decomposition is a very active research line in the incoherent decomposition topic [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past decades, this technique has been widely used in many different applications, such as land-cover classification, target detection, damage assessment, and soil moisture estimation [4]. Target decomposition mainly includes two categories: coherent decomposition of the measured Sinclair matrix, and incoherent decomposition of the measured coherency/covariance matrix [1]- [4]. Because of the diversity of scattering models and parameter inversion algorithms, model-based decomposition is a very active research line in the incoherent decomposition topic [4].…”
Section: Introductionmentioning
confidence: 99%
“…Target decomposition mainly includes two categories: coherent decomposition of the measured Sinclair matrix, and incoherent decomposition of the measured coherency/covariance matrix [1]- [4]. Because of the diversity of scattering models and parameter inversion algorithms, model-based decomposition is a very active research line in the incoherent decomposition topic [4]. The general idea of any model-based decomposition is to fit some simple physically-based scattering models to the observations.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of polarimetric scattering mechanisms is the bridge between the polarimetric synthetic aperture radar (PolSAR) measurements and both qualitative and quantitative retrieval of parameters describing physical processes on land cover [1]. According to the different ways an electromagnetic way can interact with vegetated and/or artificial targets it becomes necessary to have available mathematical and/or physical models which account for both geometrical and electromagnetic properties of matter.…”
Section: Introductionmentioning
confidence: 99%
“…As known, polarimetric target decompositions are grouped into two main categories, i.e., Sinclair matrix-based coherent approaches and coherency/covariance matrix-based incoherent ones [2]. Eigenvalue-eigenvector-based and model-based methods are two major groups belonging to incoherent decompositions [1,2]. Two comprehensive reviews of this group of techniques can be found in [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation